IMPLEMENTASI AKAD JUAL BELI PERSPEKTIF MADZHAB AL-SYAFI’I DAN KONTESTUALISASINYA PADA JUAL BELI DI PASAR TIRTAYASA SERANG - Alwani, Alwani; Pujiono, Pujiono (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2022)
The location of this study is located in Tirtayasa Serang Bnaten Market, which is the reason the area is used as the object of research is because the market has a strategic place and neatly arranged, from trading places to vehicle parking lots, then researchers are interested in the implementation time of the Market that operates only on Wednesdays and Saturdays. This writing uses field research (field research) that is by jumping in the field or research location. Data collection techniques with interviews, observations, documentation. The data from this study consists of primary data and secondary data, and is then analyzed with qualitative descriptive research methods. From the results of field research, researchers get and obtain the fact of the implementation of buying and selling in accordance with Madzhab shafi'i, some people use as in Indonesian the word